Genetics in dilated cardiomyopathy. (August 2013) - Garcia-Pavia, Pablo; Cobo-Marcos, Marta; Guzzo-Merello, Gonzalo; Gomez-Bueno, Manuel; Bornstein, Belen; Lara-Pezzi, Enrique; Segovia, Javier; Alonso-Pulpon, Luis
Discoveries made during the last 20 years have revealed a genetic origin in many cases of dilated cardiomyopathy (DCM). Currently, over 40 genes have been associated with the disease. Mutations in DCM-causing genes induce the condition through a variety of different pathological pathways with complex and not completely understood mechanisms. Genes that encode for sarcomeric, cytoskeletal, nuclear membrane, dystrophin-associated glycoprotein complex and desmosomal proteins are the principal genes involved. In this review we discuss the most frequent DCM-causing genes. We propose a classification in which DCM genes are considered as being major or minor genes according to their mutation frequency and the available supporting evidence. The main phenotypic characteristics associated with each gene are discussed.